Pengaruh Ekstrak Daun Jati (Tectona grandis L.f) Terhadap Fungsi Hati Dan Fungsi Ginjal Pada Mencit Putih Jantan - Elisma Elisma; Novi Priyoka Putra; Helmi Arifin (STIFARM Padang, 2011)
Study about sub acute toxicity of jati leaf extract toward white male mice has been done, which consist of SGPT activity for liver function test, creatinine clearance for kidney function test and organ’s weight ratio. The extract was administered orally once a day for 15, 30 and 45 days with variable dose of 150, 300 and 600 mg per kg body weight. The result showed that there were no significant effect of jati leaf extract administration to the SGPT activity, kidney function and organ’s weight ratio (p > 0.05).